Firm growth type and capital structure persistence - Wu, Xueping; Au Yeung, Chau Kin (Journal of Banking & Finance, 2012)
We find that growth type (identified by a two-way sort on firm initial market-to-book ratio and asset tangibility) can parsimoniously predict significantly dispersed and persistently distinct future leverage ratios. Growth type is persistent; growth-type-sorted cross-sections of corporate fundamental variables (such as tangible versus intangible investment style) are also meaningfully persistent. As economic and market conditions improve, low growth type firms are keener to issue new debt than equity, whereas high growth type firms are least likely to issue debt and keenest to issue equity. These findings demonstrate that firms rationally invest and seek financing in a manner compatible with their growth types. Consistent with a generalized Myers–Majluf framework, growth type compatibility enables distinct growth types and hence specifications of market imperfection or informational environments to persist. Growth type is apparently a fundamental factor for capital structure persistence.